Três obras para tímpanos solo: um estudo interpretativo - Lima, Daniel Dias de (2018)
The search for new sonorities in the 20th and 21st centuries brought new technical challenges for the performers. In this research, we try to understand the different interpretative strategies needed in pieces for solo timpani with different levels of sound investigation. Three pieces were chosen for this research: Etude Nr. 45 by Franz Krüger, March by Elliott Carter and Shuriken by Cesar Traldi. The dissertation begins with a discussion about the historical development and changes of the timpani and its repertoire, since the 18th century until now. After that, we present an analysis of compositional features and the rise of new techniques of Eight Pieces for Four Timpani by Elliott Carter, followed by a narrative about the term sound exploration. At the end we present an interpretative study focused on sound exploration on those pieces, by using the analisys as a tool to discuss the possible interpretative decisions for these pieces. Studying these pieces, we discovered different techniques to perform and that each one needs a different interpretative strategy related to the period that these pieces were composed. In fact, we improve our performance and the technical possibilities on timpani compositions.